Hubungan Sanitasi Lingkungan dan Personal Hygiene Ibu Terhadap Diare Pada Balita di Desa Sungai Lunuk Kabupaten Murung Raya - Angelina, Jessica Florencia; Lestarisa, Trilianty; Nawan (Fakultas Kedokteran Universitas Palangka Raya, 2024)
Diarrhea is a global health problem, especially in developing countries such as Indonesia. Diarrhea is caused by fecal-oral transmission of viral, bacterial, and parasitic infections, resulting in loose, mushy to liquid stools that are passed three or more times per day. In the report of the Murung Raya regency Health Office in 2021, diarrhea in toddlers was 1,858 cases. Factors that drive the occurrence of diarrhea is the environment and behavior. The mother's lack of care and knowledge in healthy living behavior, as well as unqualified home sanitation, increase the disease. Researchers were interested to know whether there is a relationship between environmental sanitation and personal hygiene of Mothers Against diarrhea in toddlers in Sungai Lunuk Village, Murung Raya regency. Analytic observational research with cross sectional approach. Result: there is a significant relationship between the habit of washing hands against diarrhea in toddlers with a value of p=0.001. Conclusion: there is a significant relationship between the habit of washing hands of Mothers Against diarrhea in toddlers in Sungai Lunuk village, while the Sewerage in Sungai Lunuk village does not qualify because there is no meaningful relationship between the Sewerage of waste water to diarrhea in toddlers in Sungai Lunuk Village.